STAINLESS STEEL COLOR CHANGE, DEPENDING ON THE LASER PARAMETERS IN LABELING PROCESS - Gribovskis, Aleksejs; Bernāns, Normunds; Počekajevs, Oskars; Narica, Pāvels (HUMAN. ENVIRONMENT. TECHNOLOGY. Proceedings of the Students International Scientific and Practical Conference, 2016)
This research describes color marking on stainless steel using various laser parameters. As a process, laser marking has been known for a long time, however, usage of this technology is rarely found for industrial needs. New fiber laser allows user to change the laser parameters in order to change color scheme, quality and visual appearance on the engraved surface.